Impact of indigenous storage systems and insect infestation on the contamination of maize with fumonisin - Fandohan, P.; Gnonlonfin, G.J.B.; Hell, K.; Marasas, W.F.O.; Wingfield, M. (2006)
Four storage systems of maize commonly used by farmers in Benin, West Africa, were tested to determine their impact on infection of maize by Fusarium and subsequent contamination with fumonisins. The study showed that Fusarium incidence was significantly higher when maize was stored on a cemented floor in a house, a non ventilated facility (40.3 ± 17.4%), than in the other tested systems (p < 0.05). The lowest Fusarium incidence was recorded when maize was stored in a bamboo granary that is a ventilated facility (25.5 ± 13.5%) (p < 0.05). All maize samples from the tested storage systems were found to be fumonisin positive, with levels ranging from 0.6 to 2.4 mg/kg. Fumonisin level, overall, was found to decrease over the storage period, but not significantly in all the tested storage systems. Damage by lepidopterous pests was significantly and positively correlated with both infection of maize with Fusarium and contamination by fumonisin. In contrary, damage by coleopterous insects was significantly and negatively correlated with infection of maize with Fusarium and contamination by fumonisin. Avoiding the use of non-ventilated systems to store maize and reducing insect infestation in field and during storage are very important recommendations for farmers.